Dopamine and noradrenaline, but not serotonin, in the human claustrum are greatly reduced in patients with Parkinson's disease: possible functional implications. (11th November 2016) - Sitte, Harald H.; Pifl, Christian; Rajput, Ali H.; Hörtnagl, Heide; Tong, Junchao; Lloyd, George K.; Kish, Stephen J.; Hornykiewicz, Oleh
Abstract: In the human brain, the claustrum is a small subcortical telencephalic nucleus, situated between the insular cortex and the putamen. A plethora of neuroanatomical studies have shown the existence of dense, widespread, bidirectional and bilateral monosynaptic interconnections between the claustrum and most cortical areas. A rapidly growing body of experimental evidence points to the integrative role of claustrum in complex brain functions, from motor to cognitive. Here, we examined for the first time, the behaviour of the classical monoamine neurotransmitters dopamine, noradrenaline and serotonin in the claustrum of the normal autopsied human brain and of patients who died with idiopathic Parkinson's disease (PD). We found in the normal claustrum substantial amounts of all three monoamine neurotransmitters, substantiating the existence of the respective brain stem afferents to the claustrum. In PD, the levels of dopamine and noradrenaline were greatly reduced by 93 and 81%, respectively. Serotonin levels remained unchanged. We propose that by virtue of their projections to the claustrum, the brain stem dopamine, noradrenaline and serotonin systems interact directly with the cortico‐claustro‐cortical information processing mechanisms, by‐passing their (parallel) routes via the basal ganglia‐thalamo‐cortical circuits. We suggest that loss of dopamine and noradrenaline in the PD claustrum is critical in the aetiology of both the motor and the non‐motor symptoms of PD. Abstract : In the human brain, the claustrum is a small subcortical telencephalic nucleus, situated between the insular cortex and the putamen. We examined the behaviour of the classical monoamine neurotransmitters in the claustrum of the normal autopsied human brain and of patients who died with idiopathic Parkinson's disease (PD). In patients, we found the levels of dopamine and noradrenaline to be greatly reduced in comparison to control. We propose that loss of dopamine and noradrenaline in the PD claustrum is critical in the aetiology of both the motor and the non‐motor symptoms of PD.